Cytosine-Functionalized Macrocyclic Receptor for Nucleotides: Combining Three Recognition Motifs - Morozov, Boris; Oshchepkov, Aleksandr; Xu, Dan; Kataev, Evgeny (European Journal of Organic Chemistry, 2023)
Nucleoside monophosphates perform various essential functions and serve as second messengers in living systems. Despite the success of nucleotide-selective probes based on proteins, the creation of synthetic receptors for nucleoside monophosphates remains a challenging task. In this paper, we explore the design of synthetic receptors based on a combination of three recognition motifs. We show that each binding motif contributes to the formation of the host-guest complexes. The core macrocycle provides recognition of the phosphate residue of the nucleotide, while naphthalimide and the attached cytosine residue participate in the coordination of the nucleobase via π-π and hydrogen bonding interactions. The presence of cytosine in the receptor structure substantially increases the overall affinity of receptors for nucleotides. A considerable increase (100-fold) in binding affinities is observed for the tetranucleotide DNA sequences 5′-GGGG -3′ and 5′-CCCC-3′, as compared to the previously reported system without the attached cytosine.
CRIS-Team Scopus Importer:2023-12-15
Keywords: anion sensing; cyclic di-GMP; guanosine; naphthalimide; nucleotide recognition

Dye-functionalized phosphate-binding macrocycles: from nucleotide to G-quadruplex recognition and "turn-on" fluorescence sensing - Oshchepkov, Aleksandr; Reznichenko, Oksana; Xu, Dan; Morozov, Boris; Granzhan, Anton; Kataev, Evgeny (Chemical Communications, 2021)
A novel strategy to design "turn-on" fluorescent receptors for G-quadruplexes of DNA is presented, which relies on the connection of phosphate binding macrocycles (PBM) with naphthalimide dyes. A new PBM-dye family was synthesized and evaluated in terms of binding and detection of nucleotides and DNA G-quadruplexes of different topologies.
CRIS-Team WoS Importer:2021-10-08

Helix-Like Receptors for Perrhenate Recognition Forming Hydrogen Bonds with All Four Oxygen Atoms - Morozov, Boris; Ravi, Anil; Oshchepkov, Aleksandr; Rueffer, Tobias; Lang, Heinrich; Kataev, Evgeny (Chemosensors, 2021)
Supramolecular recognition of perrhenate is a challenging task due to therelatively large size and low charge density of this anion. In this work, we design and synthesize a family of helix-like synthetic receptors that can bind perrhenate by forming hydrogen bonds with all four oxygen atoms of the anion. Among the investigated rigid helix-forming subunit derived from 1,1 '-ferrocenedicarboxylic acid, 1,3-phenylenediacetic acid and 2,2 '-(ethyne-1,2-diyl)dibenzoic acid, the latter one shows the best selectivity for perrhenate recognition. However, the receptor based on 1,1 '-ferrocenedicarboxylic acid demonstrates selectivity to bind chloride in a 1:2 fashion. The properties of the receptors are investigated in the acetonitrile solution by using NMR, UV-Vis, and in the solid state by single crystal X-ray analysis.
CRIS-Team WoS Importer:2021-06-04